THE GAME APPROACH TO CONTROL OF DOUBLE LINKED MANIPULATOR - Ghukasyan, A. A.; Stepanyan, V. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
For the double linked manipulator with three degrees of mobility game problems of approach-evasion with the given target set are investigated at different restrictions on controlling influences and on a minimax square-law functional. The received optimal decisions for linear model are used for control of nonlinear model with the help of an additional regulator.